Metformin Protective Effects in LPS-Induced Alzheimer's Disease Mice Model: NO-cGMP-KATP Pathway Involvement - Mojtaba Dolatshahi; Ali Khorsandinezhad; Behnam Ghorbanzadeh; Yousef Paridar; Donya Nazarinia (Acta Medica Iranica)
This project has studied the effects of metformin on cognition impairment, depression, hyperalgesia, stress oxidative and neuroinflammation in a rodent Alzheimer's disease (AD) model created via LPS (lipopolysaccharide). For defining possible mechanisms, the NO/cGMP/KATP pathway roleplay was considered.  Mice model was created via LPS treatment. Open field forced swimming and hot plate tests were done. Shuttle-box test and Y-maze test were used to assay Learning-memory. Biochemical assay compromised malondialdehyde (MDA) and TNF-alpha concentration and superoxide dismutase (SOD) activity measurement in hippocampus samples. NO-cGMP-KATP pathway contribution was assessed by its agonists/antagonist pre-treatment, 15 min before metformin (150, 200, 250 mg/kg). Initial latency (IL) was increased by LPS injection while it was reduced by metformin (250 mg), in shuttle-box test. Pretreatment with methylene blue, L-NAME and glibenclamide before metformin augmented IL, although it was diminished by L- arginine and sildenafil pretreatment. Also, metformin increased the LPS induced step through latency (STL) reduction. L-NAME, methylene blue and glibenclamide decreased the STL, but it was increased by L-arginine and sildenafil. In Y-maze test, metformin increased the LPS-induced spontaneous alternation reduction. L-NAME, methylene blue and glibenclamide decreased it. LPS added immobility time in forced swimming trial, whereas it was reduced thru metformin. L-NAME, methylene blue and glibenclamide increased the anti-depressive effect of metformin while it was attenuated via L-arginine, sildenafil and diazoxide. LPS treatment diminished the threshold of pain perception in hot-plate test, while metformin didn’t have any significant effect. Metformin reduced the LPS-induced lipid peroxidation (MDA level). But, L-NAME, methylene blue and glibenclamide worsen the lipid peroxidation, whereas it was improved by L-arginine and sildenafil. Metformin improved LPS-induced reduction in SOD activity. SOD activity was reduced by L-NAME, methylene blue and glibenclamide pre-treatment. LPS enhanced TNF-alpha amount that decreased by metformin. Pre-injection with methylene blue, L-NAME and glibenclamide increased TNF-alpha concentrations while L-arginine, sildenafil and diazoxide reduced it. Conclusions: Metformin can improve learning-memory loss, depression, hyperalgesia, neuroinflammation and oxidative stress produced by LPS and NO/cGMP/KATP pathway maybe has a roleplay.